Talking, drawing, writing : lessons for our youngest writers - Horn, Martha; Giacobbe, Mary Ellen (Portland, Me : Stenhouse Publishers, 2007)
"In Talking, Drawing, Writing: Lessons for Our Youngest Writers, Martha Horn and Mary Ellen Giacobbe invite readers to join them in classrooms where they listen, watch, and talk with children, then use what they learn to create lessons designed to meet children where they are and lead them into the world of writing, advocating for formal storytelling sessions, in which children tell about what they know, and for focused sketching sessions so that budding writers learn how to observe more carefully.". "The book's lessons are organized by topic and include oral storytelling, drawing, writing words, assessment, introducing booklets, and moving writers forward. Based on the authors' work in urban kindergarten and first-grade classes, the essence and structure of many of the lessons lend themselves to adaptation through fifth grade."--BOOK JACKET
Includes bibliographical references.
Keywords: Language arts (Primary).; Creative writing (Primary education).; Drawing -- Study and teaching (Primary).; Storytelling -- Study and teaching (Primary).